2005
DOI: 10.1007/s00167-005-0683-0
|View full text |Cite
|
Sign up to set email alerts
|

Bony and cartilaginous anatomy of the patellofemoral joint

Abstract: The patella as the largest sesamoid bone of the human body forms the patellofemoral joint with the patellar groove of the femur. The patellofemoral joint is a complex articulation with high functional and biomechanical requirements. Several anatomical variants of both patella and the trochlea exist. Multiple clinical problems of the knee may be caused by anatomical and physiological abnormalities of this joint. Exact knowledge about the anatomy, the biomechanics and the function of the patellofemoral joint is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 32 publications
1
158
2
7
Order By: Relevance
“…The lateral restraint, on the other hand, dropped at 208 flexion, then rose thereafter but to a lesser degree than the medial restraint. It is generally thought that the trochlear groove deepens in flexion and that the lateral facet is steeper and more prominent than the medial, 21 so the contrasting data in this study suggested an important role for the soft tissues in restraining patellar medial-lateral translations.…”
Section: Discussioncontrasting
confidence: 56%
“…The lateral restraint, on the other hand, dropped at 208 flexion, then rose thereafter but to a lesser degree than the medial restraint. It is generally thought that the trochlear groove deepens in flexion and that the lateral facet is steeper and more prominent than the medial, 21 so the contrasting data in this study suggested an important role for the soft tissues in restraining patellar medial-lateral translations.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, we found that cartilage stress plateaued when patella height had been corrected close to normal (InsallSalvati ratio approximately 1.0); further distalization did not provide lower values. Clinically, a low-lying patella or elevated tibiofemoral joint line also may lead to several complications such as joint stiffness, decreased ROM, and anterior knee pain [11,14,28]. Therefore, we advocate proper distalization of the tibial tubercle to correct the Insall-Salvati ratio to normal.…”
Section: Discussionmentioning
confidence: 99%
“…This is because femoral side OA in the PF joint is strongly influenced by tibio-femoral OA [26,27]. To eliminate the bias of other factors, only patella OA lesions were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%